2022
DOI: 10.1684/epd.2022.1466
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study of new‐onset refractory status epilepticus (NORSE): clinical features, timing of immunotherapy and outcomes

Abstract: Objective. To describe clinical characteristics associated with immunotherapy in patients with new-onset refractory status epilepticus (NORSE) and assess its timing and effect on outcomes at hospital discharge after six and 12 months of follow-up. Our secondary aim was to apply the cryptogenic NORSE (C-NORSE) score to subjects in order to evaluate its utility in identifying C-NORSE in our cohort. Methods. This was a retrospective single university hospital cohort study (2004)(2005)(2006)(2007)(2008)(2009)(2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Thus, patients with unexplained new onset seizures such as new onset refractory status epilepticus (NORSE) with generalized ictal EEG findings and diffuse or normal imaging findings could still benefit from these approaches. However, our logistic regression models revealed that new-onset seizures were associated with worse outcomes; thus, clinical decision-making should still be made on a case-by-case basis given the lack of high-quality evidence guiding therapy in these patients, as well as the documented role of therapies such as the ketogenic diet and immunotherapy ( 31 , 32 ). Some authors suggest the use of non-invasive neuromodulation techniques such as and transcranial magnetic stimulation (TMS) and electroconvulsive therapy (ECT) in the first week of SRSE, and consideration of neuromodulation techniques such as VNS, DBS and RNS after 2 weeks of therapy ( 33 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, patients with unexplained new onset seizures such as new onset refractory status epilepticus (NORSE) with generalized ictal EEG findings and diffuse or normal imaging findings could still benefit from these approaches. However, our logistic regression models revealed that new-onset seizures were associated with worse outcomes; thus, clinical decision-making should still be made on a case-by-case basis given the lack of high-quality evidence guiding therapy in these patients, as well as the documented role of therapies such as the ketogenic diet and immunotherapy ( 31 , 32 ). Some authors suggest the use of non-invasive neuromodulation techniques such as and transcranial magnetic stimulation (TMS) and electroconvulsive therapy (ECT) in the first week of SRSE, and consideration of neuromodulation techniques such as VNS, DBS and RNS after 2 weeks of therapy ( 33 ).…”
Section: Discussionmentioning
confidence: 94%
“…ketogenic diet and immunotherapy(31,32). Some authors suggest the use of non-invasive neuromodulation techniques such as and transcranial magnetic stimulation (TMS) and electroconvulsive therapy (ECT) in the first week of SRSE, and consideration of neuromodulation techniques such as VNS, DBS and RNS after 2 weeks of therapy (33).Although corpus callosotomy and MST remain viable options, their overall efficacy was equal or slightly inferior to neuromodulation…”
mentioning
confidence: 99%
“…Are there certain etiologies that are particularly represented in refractory SE? In other series that focused specifically on the NORSE subgroup, the most common etiology was autoimmune encephalitis, while 52% of the cases of NORSE remained cryptogenic ( 3 , 28 , 31 , 77 ). No autoimmune encephalitis was identified in our NOSE cohort although this etiology was repeatedly suspected and sought, while two cases of autoimmune encephalitis were included in our NISE group with a refractory SE.…”
Section: Discussionmentioning
confidence: 98%
“…None of the studies cited above investigated the discriminating features between NOSE and NISE. In addition, little information is available on the paraclinical aspects associated with NOSE, and the most recent publications frequently focused on the refractory subtype of these de novo SE ( 2 , 3 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous small cohort study of 18 NORSE patients found that immunotherapy including PE did not change the prognosis of NORSE patients. 34 A RCT 35 of NORSE with immunotherapy (corticosteroids, IVIG, and PE) showed that it improves the prognosis (mRS 0–2) at hospital discharge and during follow-up despite early or late application. In this study, autoimmune encephalitis was the main etiology and PE was the first-line therapy for such patients, which may cause a different result.…”
Section: Discussionmentioning
confidence: 99%